2017
DOI: 10.3892/ol.2017.7060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, biological characterization and drug sensitivity of chidamide‑resistant non‑small cell lung cancer cells

Abstract: Abstract. Chidamide, a histone deacetylase (HDAC) inhibitor, has been applied in clinical trials for various types of hematological and solid tumors. Although acquired resistance is common in chemotherapy, the mechanism of resistance to chidamide is poorly characterized. The goal of the present study was to explore, in detail, the mechanism for the induced resistance to chidamide, and investigate a potential cross-resistance to other chemotherapeutic drugs. A549 cells were exposed to gradually increasing chida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The following four classes of the HDAC family are currently known: class I HDACs (HDAC 1-3, and 8), class II HDACs (HDAC 4–7, 9, and 10), class IV (HDAC 11), and class III (sirtuin family: SIRT1-7) [ 21 , 23 ]. To date, different HDACs have been shown to be abundantly expressed in various human cancers such as laryngeal, gastric, liver, colon, breast, lung, and salivary gland cancers [ 24 , 25 , 26 ]. In salivary gland tumors, the expression of HDAC6 is correlated with a poor prognosis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following four classes of the HDAC family are currently known: class I HDACs (HDAC 1-3, and 8), class II HDACs (HDAC 4–7, 9, and 10), class IV (HDAC 11), and class III (sirtuin family: SIRT1-7) [ 21 , 23 ]. To date, different HDACs have been shown to be abundantly expressed in various human cancers such as laryngeal, gastric, liver, colon, breast, lung, and salivary gland cancers [ 24 , 25 , 26 ]. In salivary gland tumors, the expression of HDAC6 is correlated with a poor prognosis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports, CDM inhibits the proliferation of glioma cells, lung cancer, pancreatic cancer, and myeloma cells [24][25][26]. In Jurkat and HUT-78 cells, treatment with CDM (2 μM) leads to downregulation of HDAC3 expression, thus inducing necroptosis [27].…”
Section: Discussionmentioning
confidence: 82%
“…In December 2014, chidamide has been approved by the China Food and Drug Administration (CFDA) as a treatment strategy for peripheral T-cell lymphoma (PTCL) [5]. Interestingly, accumulating studies have demonstrated that chidamide shows an effective antitumor activity in multiple solid tumors, including liver cancer, colon carcinoma, and lung cancer [6][7][8][9][10][11]. In lung cancer, Hu et al have performed a phase I trial of chidamide combined with paclitaxel and carboplatin in patients with advanced NSCLC and found that a combination treatment of chidamide and paclitaxel or carboplatin was tolerated without unanticipated toxicities or pharmacokinetic interactions [6].…”
Section: Introductionmentioning
confidence: 99%